Peranan Departemen Personalia Dalam Mengurangi Jumlah Karyawan Resign Di The Westlake Resort Yogyakarta - Citra Unik Mayasari; Irma Lestari (Journal of Tourism and Economic, 2018)
The personnel department is a department that has an important role in a resort. The role personnel from the recruitment process to managing employee needs. Employees who are competent in their work are obtained and a selective personnel in the recruitment process. The result of the recruitment process will affect the quality of resources that a resort has. A qualified employee is the asset to the resort that will determine the absence of the resort. Therefore, that employeess are required to always provide the work of the optimal. Resigning or stop working is a problem which often faced by personnel at The Westlake Resort Yogyakarta. Unorganized management policies make employees choose to resign. The data collection methode used is obervastion, interview, documentation, and literature review. Data analysis method used is descriptive method. The results showed that some reasons employees to resign one of them because there was no policy against the system career. The number of employees to resign an impact on the process of resorts that has been running well.